The Equity Risk Premium Puzzle in Pakistan - Ali Sajid; Mohammad Arsalan; Muhammad Tahir Khan; Muhammad Sufyan Ramish (Market Forces, 2021)
Our study uses the consumption-based asset-pricing power utility model to test the Equity Risk Premium (ERP) puzzle in Pakistan. The study has collected monthly stock price data from July 1997 to December 2017 from the PSX data portal. We extracted information about macroeconomic factors such as inflation and risk-free interest rate from the State Bank of Pakistan. Moreover, the study used private consumption and population data from the Pakistan Bureau of Statistics. The results suggest that the ERP puzzle has a strong occurrence in Pakistan, a phenomenon previously associated with only developed markets. One disadvantage of the present investigation is the small sample size. A longer time duration could have reduced short-term biases. Past researchers have suggested different approaches for solving the equity premium puzzle. For instance, some studies used improvised structural models to justify the equity risk premium puzzle using macroeconomic factors.